Pengaruh Penggunaan Bahan Ajar Suku Bangsa di Bengkulu Terhadap Sikap Toleransi Siswa Kelas IV Sekolah Dasar Negeri 27 Kota Bengkulu - Nora Sulastri; Daimun Hambali; Wurdjinem Wurdjinem (Universitas Bengkulu, 2019)
This research was aimed to know the effect of implementation instructional material of tribe local content in Bengkulu towards the tolerance of students at seventh grade in SDN 27 Bengkulu. This research was quantitative and Quasi Experimental was used as the method. The design was The Matching only Pretest-Posttest Control Group Design. The population in this research was the students at seventh grade in SDN 27 Bengkulu and the sample was the student at seventh A grade as the experimental class and seventh B grade as control class SDN 27 Bengkulu. The instrument was questionnaire using Likert Scale, it was used through pretest and posttest. T-test (inferential analysis) was used to analyze the data in this research. The result of t-test with t- arithmetic was 1.956 and the score of t-table with signification 5 percent was 1.677. So, the researcher concluded that implementation instructional material of tribe local content influenced the tolerance of students at seventh grade in SDN 27 Bengkulu.